The Development of the Management Informatization in Lithuania - Buitkus, Almantas; Simanauskas, Leonas (Ekonomika, 1996)
The article deals with the problems of management information support in Lithuania in conjunction with the Lithuanian state information infrastructure. The most important implications for the development of management information support are formulated together with the description of the main components various level information systems and information bases. Some functional and structural requirements for the infrastructure components are presented. A certain attention is given to the concept of state information registers as a basic information component in the state information infrastructure. Several aspects of register development and usage are discussed.